Toll-like receptor agonists Porphyromonas gingivalis LPS and CpG differentially regulate IL-10 competency and frequencies of mouse B10 cells - LIU, Zhiqiang; HU, Yang; YU, Pei; LIN, Mei; HUANG, Grace; KAWAI, Toshihisa; TAUBMAN, Martin; WANG, Zuomin; Xiaozhe, HAN (Journal of Applied Oral Science, 2017)
IL-10 expressing regulatory B cells (B10) play a key role in immune system balance by limiting excessive inflammatory responses. Effects of toll-like receptor signaling and co-stimulatory molecules on B10 activity during innate and adaptive immune responses are not fully understood. Objective This study is to determine the effects of P. gingivalis LPS and CpG on B10 cell expansion and IL-10 competency in vitro. Material and Methods Spleen B cells were isolated from C57BL/6J mice with or without formalin-fixed P. gingivalis immunization. B cells were cultured for 48 hours under the following conditions: CD40L, CD40L+LPS, CD40L+CpG, and CD40L+LPS+CpG in the presence or absence of fixed P. gingivalis. Percentages of CD1dhiCD5+ B cells were measured by flow cytometry. IL-10 mRNA expression and secreted IL-10 were measured by real-time quantitative PCR and by ELISA respectively. Results P. gingivalis LPS plus CD40L significantly increased CD1dhiCD5+ B cell percentages and secreted IL-10 levels in both immunized and non-immunized mice B cells in the presence or absence of P. gingivalis, compared with control group. Secreted IL-10 levels were significantly increased in CD40L+LPS treated group compared with CD40L treatment group in the absence of P. gingivalis. CpG plus CD40L significantly decreased CD1dhiCD5+ B cell percentages, but greatly elevated secreted IL-10 levels in immunized and non-immunized mice B cells in the absence of P. gingivalis, compared with CD40L treatment group. Conclusions P. gingivalis LPS and CpG differentially enhance IL-10 secretion and expansion of mouse B10 cells during innate and adaptive immune responses.